Relationship between circulating estradiol levels, body mass index, and breakthrough bleeding in postmenopausal women receiving hormone replacement therapy - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1998)
Objective: The purpose of this prospective study was to investigate the association of breakthrough bleeding with circulating estradiol levels and obesity in postmenopausal women receiving hormone replacement therapy. Design: Fifty postmenopausal women receiving 0.625mg conjugated estrogen with 2.5mg medroxyprogesterone acetate were included in the study. Patients are recalled at Ist, 5th and 9th weeks for the measurements of the serum estradiol levels. Results: Twenty women (40%) had a bleeding episode within 9 weeks of therapy. Of the 25 women who had a body mass index (BMI) of >25, 13 (52%) had bleeding. Of the 25 women who had a BMI of <25, 7 (28%) had bleeding. There was a trend toward a relation between BMI and breakthrough bleeding, although the relation did not achieve significance (p = 0.14). Serum estradiol levels of both bleeders and nonbleeders remained similar throughout the study. Endometrial histology revealed proliferative endometrium in two cases and secretory endometrium in one case at baseline; two cases of proliferative endometrium were found during bleeding. The remaining samples revealed atrophy. Conclusions: No relation was found between serum estradiol levels and breakthrough bleeding. Nevertheless, increased BMI may have an impact on breakthrough bleeding in postmenopausal women receiving hormone replacement therapy.
Keywords: hormone replacement therapy; body mass index; bleeding; estradiol; MEDROXYPROGESTERONE ACETATE; ESTROGENS; PATTERNS